Dyskusja na temat pojęcia i istoty podatków ekologicznych - Borys, Grażyna (Discussion on the concept of ecological taxes, 2006)
The objective of the article are controversies related to the concept of ecological taxes. They refer, among others, to the problem whether an ecological function of ecological taxes is their primary function, or whether they should generate revenues aimed at environmental protection, or whether directing traditional taxes towards pro-ecological goals is sufficient for them to become ecological taxes and whether the fact of taxed object relation to environmental components (environmental services) is enough to be referred to as ecological tax? Solving the above controversies facilitates coming up with a correct difinition of ecological tax.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 50-59